Patient assessment of constipation quality of life questionnaire: validity and reliability for Indonesian population (Faculty of Medicine Universitas Indonesia, 2019)
BACKGROUND Constipation is a condition commonly encountered by physicians, causing a significant reduction in patients' quality of life. Therefore, successful management of constipation should also include increase the quality of life. The Patient Assessment of Constipation Quality of Life (PAC-QOL) questionnaire is a questionnaire developed to address this issue. However, this questionnaire had not been translated into the Indonesian language. This study was aimed to adapt PAC-QOL into Indonesian culture and perform the psychometric evaluation. METHODS Translation and cultural adaptation were performed based on the linguistic validation guidelines by Acquadro et al in 2012. To perform the psychometric evaluation, a total of 64 subjects in Petamburan district in Jakarta, Indonesia, were recruited from February to March 2018. Test-retest reliability was assessed by completing the PACQOL twice with one-week interval. Subjects also completed the Short Form 36 (SF-36) Health Survey Questionnaire to assess concurrent validity. Internal consistency was analyzed with Cronbach's alpha value (>0.7) and the intraclass correlation coefficient. RESULTS The mean (standard deviation) overall average score was 1.52 (0.66), while the Cronbach's alpha value for the overall average score was 0.910. Concurrently, the intraclass correlation coefficient for the overall score was 0.87. Simultaneously, several experts judged content validity to be adequate. All the questions had significant correlations with their respective domains. Moreover, each domain of PAC-QOL also had a significant correlation with several SF-36 domains. CONCLUSIONS The psychometric evaluation performed in this study demonstrated that the Indonesian version of the PAC-QOL was valid and reliable, suggesting that this questionnaire can be used in daily clinical practice.